The influence of desiccation, cryopreservation and rehydration on the survival of polyembryonic Citrus seeds - Graiver, Natalia Gisel (2012)
Three categories of seed storage behavior are generally recognized among plant species: orthodox, intermediate and recalcitrant. Intermediate seeds, such as Citrus, can withstand partial dehydration, but they cannot be stored under conventional genebank conditions because they are cold-sensitive and desiccation does not increase their longevity. Citrus seeds that are immersed in liquid nitrogen (LN) without a previous dehydration process show a very low viability; therefore the water content when they are immersed in LN is considered as the most critical factor in cryopreservation process. The purpose of this study was to investigate the basis of the optimal hydration status for cryopreservation of intermediate oily Citrus seeds: Citrus sinensis (sweet orange) and Citrus paradise (grapefruit). In the present work two conditions were tested: a) seed desiccation, b) seed desiccation followed by LN treatment with thawing under controlled conditions. In addition two pre-sowing (preheating and prehumidification procedures previous to the germinability test) were applied and their influences on the viability of the seeds were analyzed. In the cases of seeds that were only dried and in seeds that were dried and treated with LN, the tested pre-sowing treatments (pre-humidification or heating) did not significantly improve the viability of the seeds with respect to the control samples (P <0.05); in fact preheating deteriorated significantly the viability of the LN treated seeds. The survival of Citrus sinenis and Citrus paradise seeds, submitted to cryopreservation in LN was examined and seed desiccation sensitivity following rehydration procedures was quantified. Results showed that in order to reach the maximum viability, the seeds exposed to LN , must be first dehydrated to a range of ERH 69-81% (0.16-0.31 gH2O g -1dry basis) for Citrus sinensis and 69-75% (0.09-0.11 gH2Og -1dry basis) for Citrus paradise. The limit of hydration for LN Citrus seeds treatment corresponded to the unfrozen water content in the tissue, confirming that seed moisture should be reduced to such an extent to avoid the formation of intra-cellular ice crystals during ultra-rapid freezing, thus preserving the integrity of seed tissues.